Mycotoxins: detection methods, management, public health and agricultural trade - Leslie, J. F; Bandyopadhyay, R; Visconti, A (Mycotoxins: detection methods, management, public health and agricultural trade, 2008)
Mycotoxins are produced worldwide by several fungi on a wide range of agricultural commodities and are closely related to human and animal food chains. Examining mycotoxins and their impact from a public health viewpoint, this book provides an overview and introduction to the subject and examines the health, trade and legislation issues involved. Management of mycotoxins is discussed in detail as well as the global problems caused by mycotoxins.